Full-perovskite laminated solar cell and preparation method thereof
By designing periodic micro-nano structures on the transparent substrate of all-perovskite tandem solar cells, the problem of large light reflection loss was solved, resulting in increased photocurrent and enhanced light absorption capacity. This simplified the fabrication process and reduced costs.
Patent Information
- Application Number
- CN202411818801.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional all-perovskite tandem solar cells suffer from significant internal light reflection losses, which severely limits the increase in photocurrent.
Periodically varying micro/nano structures, such as serrated or sinusoidal structures, are designed on the side of the transparent substrate away from the incident light, and electrodes and functional layers are covered on it using conformal growth technology to reduce light reflection loss.
It significantly improves the light absorption capability across the entire working spectrum, greatly enhances the photocurrent, and has a simple device structure that is easy to fabricate, thus reducing production costs.
Smart Images

Figure CN119277883A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to an all-perovskite stacked solar cell and a preparation method thereof. Background Art
[0002] Solar cells can directly convert light energy into electrical energy, reduce dependence on limited fossil fuels, and provide strong support for the implementation of energy diversification strategies. Compared with silicon, perovskite materials have the advantages of continuously adjustable band gaps, can be produced through low-cost manufacturing technologies such as solution processing or printing methods, and can be used to prepare flexible devices. The stacking technology vertically stacks solar cell materials with different band gaps to more efficiently capture and convert different parts of the solar spectrum. This design allows the stacked cells to absorb sunlight over a wider band and effectively reduce the thermal loss of high-energy photons, thereby providing higher photoelectric conversion efficiency than traditional single-junction solar cells. Therefore, all-perovskite stacked solar cells have huge application potential and market competitiveness in the future photovoltaic field, and are expected to surpass traditional silicon-based solar cells in cost and efficiency.
[0003] Traditional solar cells often use a multi-layer flat film stacked structure, which easily causes interference effects of light inside the cell, resulting in large light reflection energy loss, which seriously limits the conversion efficiency. Due to its material properties, silicon solar cells can prepare pyramid-shaped micro-nano structures inside the cell through chemical etching and other means. This micro-nano structure can effectively reduce light reflection losses and greatly improve the photocurrent, thereby increasing the conversion efficiency of solar cells. However, due to the significant differences between the materials and production processes used in perovskite solar cells and traditional silicon solar cells, the pyramid-shaped micro-nano structures used in traditional silicon solar cells cannot be implemented in all-perovskite stacked cells. Therefore, finding a method to reduce reflected light loss suitable for all-perovskite stacked solar cells has become a hot spot in current technological development.
[0004] The current highest record of all-perovskite tandem solar cell efficiency is 29.1%. However, this is still a long way from the theoretical limit, and the main factor affecting the efficiency of tandem devices is the large light reflection loss inside the tandem cell, which severely limits the increase in photocurrent. Therefore, it is urgent to find a solution to reduce the light loss of tandem cells and increase their photocurrent to further promote the development of all-perovskite tandem cells. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the problem to be solved by the present invention is that the internal light reflection loss of the traditional stacked battery is large, which seriously limits the improvement of the photocurrent.
[0007] To solve the above technical problems, in a first aspect, the present invention provides the following technical solutions: a full perovskite stacked solar cell, comprising a transparent substrate layer, a first electrode layer and a first wide bandgap sub-cell functional layer stacked in sequence along the direction of incident light; the side of the transparent substrate layer away from the incident light is a velvet surface; the first electrode layer is uniformly covered on the transparent substrate layer; the first wide bandgap sub-cell functional layer is uniformly covered on the first electrode layer; the first electrode layer is a transparent electrode.
[0008] As a preferred solution of the all-perovskite tandem solar cell of the present invention, the cross-sectional shape of the transparent substrate layer on the side away from the incident light changes periodically.
[0009] As a preferred solution of the all-perovskite tandem solar cell of the present invention, the cross-sectional shape of the side of the transparent substrate layer away from the incident light is sawtooth-shaped.
[0010] As a preferred solution of the all-perovskite tandem solar cell of the present invention, the cross-sectional shape of the transparent substrate layer on the side away from the incident light changes sinusoidally.
[0011] As a preferred solution of the all-perovskite tandem solar cell described in the present invention, it also includes a wide bandgap perovskite layer, a second wide bandgap sub-cell functional layer, a carrier recombination layer, a first narrow bandgap sub-cell functional layer, a narrow bandgap perovskite layer, a second narrow bandgap sub-cell functional layer and a second electrode layer stacked in sequence on the first wide bandgap sub-cell functional layer.
[0012] As a preferred solution of the all-perovskite tandem solar cell described in the present invention, the cross-sectional shape of the transparent substrate layer on the side away from the incident light is a periodic sawtooth structure with a period of 200nm and a peak-to-valley height difference of 150nm.
[0013] As a preferred solution of the all-perovskite tandem solar cell described in the present invention, the cross-sectional shape of the transparent substrate layer on the side away from the incident light is a periodic sinusoidal structure with a period of 200nm and a peak-to-valley height difference of 150nm.
[0014] On the other hand, the present invention also provides a method for preparing an all-perovskite tandem solar cell, which is used to prepare the above-mentioned all-perovskite tandem solar cell, and the preparation method includes forming a velvet micro-nano structure on the side of the transparent substrate layer away from the incident light; conformally growing a first electrode layer on the transparent substrate layer; and conformally growing a first wide bandgap sub-cell functional layer on the first electrode layer.
[0015] As a preferred solution of the method for preparing the all-perovskite tandem solar cell of the present invention, the velvet micro-nano structure is a periodic sawtooth structure.
[0016] As a preferred solution of the method for preparing the all-perovskite tandem solar cell of the present invention, the velvet micro-nano structure is a periodic sinusoidal structure.
[0017] The beneficial effects of the present invention are as follows: the anti-reflection effect of the micro-nano structure provided by the present invention is stable and is applicable to all-perovskite stacked solar cells of various materials and configurations; it can significantly improve the light absorption capacity of the working spectrum band of the solar cell, greatly improve the photocurrent, and the device structure is simple, easy to prepare, and highly repeatable. There is no need to introduce additional process flow to make the perovskite and the micro-nano structure conformally grow, which significantly reduces the technical requirements and production costs of the production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is a hierarchical structure diagram of the all-perovskite tandem solar cell with a sawtooth micro-nano structure described in Example 2.
[0020] Figure 2 Schematic diagram of the internal light coupling mechanism of a planar all-perovskite tandem solar cell.
[0021] Figure 3 Reflection spectrum of a planar all-perovskite tandem solar cell.
[0022] Figure 4 The absorption curves corresponding to the tentative micro-nanostructure period, the tentative wide bandgap perovskite layer thickness, and different peak-to-valley differences in Example 2 are shown.
[0023] Figure 5 The absorption curves corresponding to different wide bandgap perovskite layer thicknesses with a fixed peak-to-valley difference and a tentative micro-nanostructure period in Example 2.
[0024] Figure 6 This is a reflectivity curve corresponding to different micro-nanostructure periods when the peak-to-valley difference and the wide bandgap perovskite layer thickness are fixed in Example 2.
[0025] Figure 7 This is a comparison chart of the external quantum efficiency (EQE) of the all-perovskite tandem solar cell using a planar structure and the cell using a sawtooth micro-nano structure in Example 2.
[0026] Figure 8This is a comparison chart of the reflectivity of the all-perovskite tandem solar cell using a planar structure and the cell using a sawtooth micro-nano structure in Example 2.
[0027] Fig. 9 This is a graph showing the relationship between the absorption curve of the all-perovskite tandem battery in the long-wave band and the thickness of the wide-bandgap perovskite film in Example 2.
[0028] Fig.10 This is a hierarchical structure diagram of the all-perovskite tandem solar cell with a sinusoidal micro-nano structure described in Example 3.
[0029] Fig.11 The absorption curves corresponding to the tentative micro-nanostructure period, the tentative wide bandgap perovskite layer thickness, and different peak-to-valley differences in Example 3 are shown.
[0030] Fig.12 The absorption curves corresponding to different wide bandgap perovskite layer thicknesses with a fixed peak-to-valley difference and a tentative micro-nanostructure period in Example 3.
[0031] Fig.13 The reflectivity curves corresponding to different micro-nanostructure periods when the peak-to-valley difference and the wide bandgap perovskite layer thickness are fixed in Example 3.
[0032] Fig.14 This is a comparison chart of the external quantum efficiency (EQE) of the all-perovskite tandem solar cell using a planar structure and the cell using a sinusoidal micro-nano structure in Example 3.
[0033] Fig.15 This is a comparison chart of the reflectivity of the all-perovskite tandem solar cell using a planar structure and the cell using a sinusoidal micro-nano structure in Example 3.
[0034] Fig.16 This is a graph showing the relationship between the absorption curve of the all-perovskite tandem battery in the long-wave band and the thickness of the wide-bandgap perovskite film in Example 3.
[0035] In the figure: 100, transparent substrate layer; 200, first electrode layer; 300, first wide bandgap sub-battery functional layer; 400, wide bandgap perovskite layer; 500, second wide bandgap sub-battery functional layer; 600, carrier recombination layer; 700, first narrow bandgap sub-battery functional layer; 800, narrow bandgap perovskite layer; 900, second narrow bandgap sub-battery functional layer; 1000, second electrode layer. DETAILED DESCRIPTION
[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings.
[0037] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0038] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it an embodiment that is mutually exclusive with other embodiments, either individually or selectively.
[0039] Example 1, reference Figure 1 and Figure 2 , which is the first embodiment of the present invention, and provides a full perovskite tandem solar cell. Figure 1 The all-perovskite stacked solar cell includes a transparent substrate layer 100, a first electrode layer 200, a first wide bandgap sub-cell functional layer 300, a wide bandgap perovskite layer 400, a second wide bandgap sub-cell functional layer 500, a carrier recombination layer 600, a first narrow bandgap sub-cell functional layer 700, a narrow bandgap perovskite layer 800, a second narrow bandgap sub-cell functional layer 900 and a second electrode layer 1000 stacked in sequence along the direction of incident light.
[0040] Among them, the transparent substrate layer 100 is photovoltaic glass, and the back surface of the photovoltaic glass away from the incident light has a velvet micro-nano structure, that is, a non-planar micro-nano structure, which can be obtained by various micro-nano processing methods such as electron beam lithography technology, and the cross-sectional shape of the velvet micro-nano structure includes but is not limited to a sawtooth grating, a sinusoidal grating, etc. The specific micro-nano configuration must be finely controlled to achieve a significant anti-reflection effect and a wide spectral band, and can be finely adjusted for different battery structures by studying the spectral characteristics of thin-film batteries.
[0041] The first electrode layer 200 is a transparent electrode, and its thickness uniformly covers the velvet surface of the transparent substrate layer 100, that is, conformally grows with the velvet surface micro-nanostructure. The optional materials include but are not limited to indium tin oxide (ITO), fluorine-doped tin oxide (FTO), and indium zinc oxide (IZO).
[0042] The first wide bandgap subcell functional layer 300 uniformly covers the first electrode layer 200, that is, conformally grows with the first electrode layer 200. This layer can be an electron transport layer or a hole transport layer, and the material can be selected from the electron transport layer materials and hole transport layer materials commonly used in perovskite cells.
[0043] The wide bandgap perovskite layer 400 can be grown on the first wide bandgap sub-cell functional layer 300 by conventional preparation processes (such as spin coating), and does not need to be conformally grown with the first wide bandgap sub-cell functional layer 300. The material is a commonly used wide bandgap perovskite material.
[0044] The second wide bandgap sub-battery functional layer 500, the carrier recombination layer 600, the first narrow bandgap sub-battery functional layer 700, the narrow bandgap perovskite layer 800, the second narrow bandgap sub-battery functional layer 900 and the second electrode layer 1000 are all prepared according to conventional preparation processes, and the materials are all materials with corresponding functions commonly used in perovskite batteries.
[0045] It is worth noting that when light is incident on the interface of different media, refraction and reflection will occur. In different media, the propagation, refraction and reflection of light will introduce complex phase changes, thus producing coherence phenomena. The structure of traditional all-perovskite stacked cells is a multi-layer planar thin film stack structure, which causes complex coherence processes to occur inside the light, increasing the loss of reflected light due to coherence phenomena, resulting in serious energy loss.
[0046] Therefore, the present invention analyzes the physical mechanism of light propagation inside the all-perovskite tandem battery and finds that the coupling-enhanced reflection loss of light can be mainly divided into the following two processes: First, in the wavelength range of 300-700 nm, photons are mainly absorbed by the wide bandgap perovskite layer 400. Figure 2 As shown on the left, incident light 1 within this wavelength range generates reflected light 1 at the interface between the transparent substrate layer 100 and the first electrode layer 200, generates reflected light 2 at the interface between the first electrode layer 200 and the first wide band gap sub-cell functional layer 300, and generates reflected light 3 at the interface between the first wide band gap sub-cell functional layer 300 and the wide band gap perovskite layer 400.
[0047] The phases of reflected light 2 and reflected light 3 are mainly regulated by the first electrode layer 200 during the propagation process. Finally, reflected light 2, reflected light 3 and reflected light 1 are coherently enhanced inside the transparent substrate layer 100, resulting in enhanced reflected light loss. Specifically, Figure 3 Several reflection peaks within the wavelength range of 300-700 nm are shown, and the characteristic wavelengths corresponding to the reflection peaks are mainly regulated by the first electrode layer 200 .
[0048] Secondly, in the wavelength range of 700~900nm, photons are mainly absorbed by the narrow bandgap perovskite layer 800. Figure 2 As shown on the right side, incident light 2 within this wavelength range generates reflected light 4 at the interface between the first wide bandgap sub-cell functional layer 300 and the wide bandgap perovskite layer 400 .
[0049] Since the incident light 2 passes through the multi-layer interfaces among the wide bandgap perovskite layer 400 , the second wide bandgap subcell functional layer 500 , the carrier recombination layer 600 , the first narrow bandgap subcell functional layer 700 and the narrow bandgap perovskite layer 800 , complex reflected light is generated.
[0050] For the convenience of theoretical explanation, these reflected lights are combined and processed as reflected light 5. The phase of reflected light 5 is mainly regulated by the wide bandgap perovskite layer 400. Finally, reflected light 5 and reflected light 4 are coherently enhanced inside the first wide bandgap sub-cell functional layer 300, resulting in enhanced reflected light loss. Figure 3 The single or multiple reflection peaks in the wavelength range of 700-900 nm are shown. The characteristic wavelength of the reflection peak is mainly controlled by the wide bandgap perovskite layer 400.
[0051] It is not difficult to find that both light reflection coupling enhancement processes occur before the wide bandgap perovskite layer 400. Considering that the first electrode layer 200 is usually prepared by magnetron sputtering technology, and the first wide bandgap sub-cell functional layer 300 is usually prepared by atomic deposition technology, these two preparation processes can achieve conformal growth of thin films and micro-nano structures without adding additional steps. Therefore, designing a micro-nano structure on the transparent substrate layer 100 is obviously a preferred solution, which can not only eliminate reflected light in the 300~700nm band range, but also break coherent coupling in the 700~900nm band range to improve light absorption.
[0052] The principle of the effect produced by the micro-nano structure of the present invention is: (1) In the 300-700 nm band, the micro-nanostructure on the back surface of the transparent substrate layer 100 plays a light trapping role: the incident light will be reflected and transmitted multiple times between the micro-nanostructures, and the reflected light will be incident on the micro-nanostructure again each time. Through multiple reflections and transmissions, the transmittance of light is maximized and the reflected light is eliminated.
[0053] (2) In the 700-1100nm band, complex reflected light coherent coupling enhancement occurs inside the all-perovskite stacked cell, resulting in coherent enhancement of reflected light. At this time, the micro-nano structure plays a role in adjusting the thickness of the wide-bandgap perovskite layer, dividing the entire cell into countless sub-cells with different wide-bandgap perovskite layer thicknesses. Since the characteristic wavelength of the reflection peak is mainly regulated by the thickness of the wide-bandgap perovskite layer 400, the micro-nano structure can achieve uniform distribution of the characteristic wavelength of the reflection peak of each sub-cell within the wavelength range of 700-1000nm, which generally weakens the influence of the reflected light coherent enhancement effect on light absorption. At this time, the entire cell presents a higher and more uniform light absorption.
[0054] Example 2, reference Figure 1 and Figure 3~Figure 9, which is the second embodiment of the present invention, and is based on the previous embodiment. This embodiment also provides a full perovskite stacked solar cell, and its hierarchical structure is the same as that of Example 1. The difference from Example 1 is that this embodiment specifically provides a transparent substrate layer 100 with a sawtooth grating micro-nano structure on the back.
[0055] Specifically, refer to Figure 1 The cross-sectional shape of the suede micro-nano structure on the back surface of the transparent substrate layer 100 is a periodically changing sawtooth shape.
[0056] The first electrode layer 200 is uniformly covered on the back surface of the transparent substrate layer 100 , and its cross-sectional shape is also periodically sawtooth-shaped, that is, it grows conformally with the periodically sawtooth-shaped structure on the back surface of the transparent substrate layer 100 .
[0057] The first wide bandgap sub-cell functional layer 300 also covers the first electrode layer 200 with uniform thickness, and its cross-sectional shape is also periodically sawtooth-shaped, that is, it grows conformally with the periodically sawtooth-shaped structure of the first electrode layer 200 .
[0058] Among them, the transparent base layer 100 with a serrated micro-nano structure provided in this embodiment is obtained through a large number of experiments and theoretical calculations. It is a structure that can realize the functions of short-wavelength light trapping and long-wavelength regulation of the thickness of wide-bandgap perovskite films and is easy to prepare. Its preferred dimensions are a period of 200nm and a peak-to-valley difference of 150nm.
[0059] The specific optimization process is: First, the peak-to-valley value of the sawtooth grating micro-nanostructure is optimized to achieve stable absorption rate in the long-wave band. The specific optimization steps are: temporarily set the grating structure period to a larger value, here set to 1000nm, and temporarily set the thickness of the wide-bandgap perovskite layer, here set to 420nm, and adjust the peak-to-valley difference of the sawtooth structure. The results are as follows: Figure 4 As shown, it can be seen that the results are better when the peak-to-valley difference is in the range of 150-200 nm. In this embodiment, the peak-to-valley difference of the sawtooth structure is selected to be 150 nm.
[0060] Secondly, the thickness of the wide band gap perovskite layer 400 is optimized to achieve a high level of absorption rate in the long-wave band. The specific optimization steps are: fix the peak-to-valley difference to 150nm, the period is temporarily set to 1000nm, and adjust the thickness of the wide band gap perovskite layer 400. The results are as follows: Figure 5 As shown, it can be seen that the wide bandgap perovskite layer 400 has better results when the thickness is in the range of 400-450 nm. In this embodiment, the wide bandgap perovskite layer 400 is selected to have a thickness of 450 nm.
[0061] Secondly, the period of the sawtooth grating micro-nanostructure is optimized to achieve an extremely low reflectivity in the short-wave band. The specific optimization steps are: fix the peak-to-valley difference to 150nm, the thickness of the wide-bandgap perovskite layer to 400nm, and adjust the sawtooth grating period. The results are as follows: Figure 6 As shown, it can be seen that when the period is less than 200nm, the reflectivity in the short-wave band has reached an extremely low level. Although the reflectivity is better at a period of 100nm, considering the limitations of the perovskite spin coating process in subsequent steps, too small a period will cause the angle of the grating structure to be too small, which is not conducive to the growth of wide-bandgap perovskite films. Therefore, a period of 200nm is selected as a better choice.
[0062] Therefore, the specific configuration of the sawtooth grating micro-nano structure determined after optimization is a periodic sawtooth structure with a period of 200nm and a peak-to-valley height difference of 150nm.
[0063] Preferably, the first electrode layer 200 is made of indium tin oxide (ITO) with a thickness of 150 nm and is conformally grown with the sawtooth grating structure.
[0064] The material of the first wide bandgap sub-cell functional layer 300 is NiO x , with a thickness of 10 nm, and conformally grown with the first electrode layer 200 .
[0065] Wide bandgap perovskite layer 400 material is FA 0.8 Cs 0.2 Pb(I 0.6 Br 0.4 )3, spin coating on the first wide bandgap sub-battery functional layer 300, after the growth is completed, the rear surface of the film is flat, according to the above optimization results, the thickest thickness is 450nm, the thinnest thickness is 300nm.
[0066] The second wide bandgap subcell functional layer 500 comprises C 60 The thickness of the thin film and SnO2 thin film is 20nm.
[0067] The material of the carrier recombination layer 600 is indium zinc oxide (IZO) and has a thickness of 40 nm.
[0068] The material of the first narrow bandgap sub-battery functional layer 700 is PEDOT:PSS, and the thickness is 30 nm.
[0069] Narrow bandgap perovskite layer 800 material is FA 0.7 MA 0.3 Pb 0.5 Sn 0.5 I3, thickness is 1000nm.
[0070] The second narrow bandgap subcell functional layer 900 comprises C 60The thickness of the 20nm and 7nm thin films are respectively.
[0071] The second electrode layer 1000 is made of copper and has a thickness of 150 nm.
[0072] In this embodiment, the indicators for evaluating the effect of the micro-nano structure include external quantum efficiency (EQE) and reflectivity.
[0073] External quantum efficiency (EQE) is defined as the ratio of the number of photoelectrons generated per unit time to the number of incident photons at a specific wavelength. Assuming that the perovskite material absorbs one photon and excites one electron, the expression is: ,
[0074] The higher the external quantum efficiency (EQE), the more photons are absorbed by the perovskite, that is, the stronger the light absorption ability, the less reflected light loss, and the greater the photocurrent generated.
[0075] Reflectivity is defined as the ratio of incident light intensity to total reflected light intensity, expressed as: ,
[0076] Reflectivity varies with wavelength, and lower overall reflectivity indicates lower light loss in the device.
[0077] Reference Figure 7 Under the same light power, the total current density of the planar structured all-perovskite tandem solar cell is 33.2184 mA / cm 2 There are three reflection peaks in the wavelength range of 300~900nm, with reflectivity of 0.17 at 350nm, 0.09 at 590nm, and 0.18 at 780nm. Figure 8 shown.
[0078] In order to break the light absorption loss in the 680-900nm band caused by the coherence effect, while maintaining the light trapping effect in the 300-680nm band, and further considering the repeatability, processing difficulty and yield rate of the micro-nano structure in the actual production process, the present invention uses a large number of experimental calculations to finely design the specific configuration of the micro-nano structure, and finally obtains a sawtooth micro-nano structure. The sawtooth micro-nano structure achieves a high absorption rate of the battery in the 680-900nm band by strictly adjusting the change amount and change rate of the wide bandgap perovskite film thickness.
[0079] Reference Figure 7 The total current density of the all-perovskite tandem solar cell using a sawtooth micro-nanostructure is 34.6367 mA / cm 2In the range of 300~680nm, the sawtooth micro-nanostructure plays a role in light trapping, successfully achieving extremely low reflectivity, greatly improving the absorption rate of the battery in this band. Fig. 9 In the range of 680-900nm, the sawtooth micro-nanostructure plays a role in regulating the thickness of the wide-bandgap perovskite film. It can be seen that in this band, the shape of the absorptivity curve is highly correlated with the thickness of the wide-bandgap perovskite film. The micro-nanostructure successfully obtains a high-level and stable absorptivity curve by finely controlling the change amount and change rate of the wide-bandgap perovskite film thickness.
[0080] Example 3, reference Figure 10~Figure 16 , which is the third embodiment of the present invention, and is based on the first two embodiments. This embodiment also provides a full perovskite tandem solar cell, whose hierarchical structure is the same as that of Example 1. The difference from Example 1 is that this embodiment specifically provides a transparent substrate layer 100 with a sinusoidal grating micro-nano structure on the back.
[0081] Specifically, refer to Fig.10 The cross-sectional shape of the suede micro-nano structure on the back surface of the transparent substrate layer 100 is a periodically changing sinusoidal shape.
[0082] The first electrode layer 200 is uniformly covered on the back surface of the transparent substrate layer 100 , and its cross-sectional shape is also periodically sinusoidal, that is, it grows conformally with the periodically sinusoidal structure on the back surface of the transparent substrate layer 100 .
[0083] The first wide bandgap sub-battery functional layer 300 also covers the first electrode layer 200 with uniform thickness, and its cross-sectional shape is also sinusoidal with periodic changes, that is, it grows conformally with the periodic sinusoidal structure of the first electrode layer 200 .
[0084] Among them, the transparent base layer 100 of the sinusoidal micro-nano structure provided in this embodiment is obtained through a large number of experiments and theoretical calculations. It is a structure that can realize short-wavelength light trapping and long-wavelength regulation of wide-band gap perovskite film thickness and is easy to prepare. Its preferred dimensions are a period of 200nm and a peak-to-valley difference of 150nm.
[0085] The specific optimization process is: First, optimize the peak-to-valley value of the sinusoidal grating micro-nanostructure to achieve stable absorption rate in the long-wave band. The specific optimization steps are: temporarily set the grating structure period to a larger value, here set to 1000nm, and temporarily set the thickness of the wide-bandgap perovskite layer to 400, here set to 440nm, and adjust the peak-to-valley difference of the sinusoidal structure. The results are as follows: Fig.11 As shown, it can be seen that the results are better when the peak-to-valley difference is in the range of 150-200nm. After combining the AM1.5 spectrum analysis, the peak-to-valley difference of the sinusoidal structure selected in this embodiment is 150nm.
[0086] Secondly, the thickness of the wide band gap perovskite layer 400 is optimized to achieve a high level of absorption rate in the long-wave band. The specific optimization steps are: fix the peak-to-valley difference to 150nm, the period is temporarily set to 1000nm, and adjust the thickness of the wide band gap perovskite layer 400. The results are as follows: Fig.12 As shown, it can be seen that the wide band gap perovskite layer thickness has better results in the range of 440~480nm. Combined with AM1.5 spectrum analysis, the wide band gap perovskite layer thickness is selected to be 480nm.
[0087] Secondly, the period of the sinusoidal grating micro-nanostructure is optimized to achieve an extremely low reflectivity in the short-wave band. The specific optimization steps are: fix the peak-to-valley difference to 150nm, the thickness of the wide-bandgap perovskite layer to 400nm, and adjust the sinusoidal grating period. The results are as follows: Fig.13 As shown, it can be seen that when the period is less than 200nm, the reflectivity in the short-wave band has reached an extremely low level. Although the reflectivity is better at a period of 100nm, considering the limitations of the perovskite spin coating process in subsequent steps, too small a period will cause the angle of the grating structure to be too small, which is not conducive to the growth of wide-bandgap perovskite films. Therefore, a period of 200nm is selected as a better choice.
[0088] Therefore, the specific configuration of the sinusoidal grating micro-nano structure determined after optimization is a sinusoidal curve with a cross-section period of 200 nm and a peak-to-valley difference of 150 nm.
[0089] Preferably, the first electrode layer 200 is made of indium tin oxide (ITO) with a thickness of 150 nm and is conformally grown with the sinusoidal grating structure.
[0090] The material of the first wide bandgap sub-cell functional layer 300 is NiO x , with a thickness of 10 nm, and conformally grown with the first electrode layer 200 .
[0091] Wide bandgap perovskite layer 400 material is FA 0.8 Cs 0.2 Pb(I 0.6 Br 0.4 )3, spin coating on the first wide bandgap sub-battery functional layer 300, after the growth is completed, the rear surface of the film is flat, the thickest part is 480nm, and the thinnest part is 330nm.
[0092] The second wide bandgap subcell functional layer 500 comprises C 60 The thickness of the thin film and SnO2 thin film is 20nm.
[0093] The material of the carrier recombination layer 600 is gold, and the thickness is 0.4 nm.
[0094] The material of the first narrow bandgap sub-battery functional layer 700 is PEDOT:PSS, and the thickness is 30 nm.
[0095] Narrow bandgap perovskite layer 800 material is FA 0.7 MA 0.3 Pb 0.5 Sn 0.5 I3, thickness is 1000nm.
[0096] The second narrow bandgap subcell functional layer 900 comprises C 60 The thickness of the 20nm and 7nm thin films are respectively.
[0097] The second electrode layer 1000 is made of copper and has a thickness of 150 nm.
[0098] In this embodiment, the index for evaluating the effect of the micro-nano structure is the same as that in Embodiment 2.
[0099] Reference Fig.14 Under the same light power, the total current density of the all-perovskite tandem solar cell using a planar structure is 33.1016 mA / cm 2 There are three reflection peaks in the wavelength range of 300~900nm, with reflectivity of 0.17 at 350nm, 0.09 at 650nm, and 0.15 at 800nm. Fig.15 shown.
[0100] In order to break the light absorption loss in the 680-900nm band caused by the coherence effect, while maintaining the light trapping effect in the 300-680nm band, and further considering the repeatability, processing difficulty and yield rate of the micro-nano structure in the actual production process, the present invention uses a large number of experimental calculations to finely design the specific configuration of the micro-nano structure, and finally obtains a sinusoidal micro-nano structure. The sinusoidal micro-nano structure achieves a high absorption rate of the battery in the 680-900nm band by strictly adjusting the change amount and change rate of the wide bandgap perovskite film thickness.
[0101] Reference Fig.14 The total current density of the all-perovskite tandem solar cell using the sinusoidal micro-nanostructure is 34.6460 mA / cm 2 In the range of 300~680nm, the sinusoidal micro-nanostructure plays a role in trapping light, successfully obtaining extremely low reflectivity, greatly improving the absorption rate of the battery in this band. In the range of 680~900nm, the sinusoidal micro-nanostructure plays a role in regulating the thickness of the wide-bandgap perovskite film. It can be seen that in this band, the shape of the absorption rate curve is highly correlated with the thickness of the wide-bandgap perovskite film, such as Fig.16As shown. The micro-nano structure successfully obtains a high-level and stable absorption rate curve by finely controlling the change amount and change rate of the wide-bandgap perovskite film thickness.
[0102] Embodiment 4: This embodiment provides a method for preparing an all-perovskite tandem solar cell, which is used to prepare the all-perovskite tandem solar cell described in Embodiment 2, and the method comprises: S1: A sawtooth grating micro-nano structure is etched on a photovoltaic glass substrate by electron beam lithography technology to obtain a transparent base layer 100 having a sawtooth grating micro-nano structure on the back side.
[0103] S2: Sputter a layer of ITO transparent thin film electrode with a thickness of 150 nm on the photovoltaic glass with the sawtooth grating micro-nano structure by magnetron sputtering technology. Due to the characteristics of magnetron sputtering technology, the thin film grows conformally with the sawtooth grating structure to obtain the first electrode layer 200.
[0104] S3: Deposit a layer of NiO on the ITO transparent thin film electrode using atomic layer deposition technology x The hole transport layer has a thickness of 10 nm. Due to the characteristics of the atomic layer deposition technology, this thin film grows conformally with the ITO transparent thin film electrode to obtain the first wide bandgap sub-battery functional layer 300.
[0105] S4: Spin-coat a wide bandgap perovskite film on the substrate by a two-step method, and then evaporate the excess solvent by a two-step annealing method. Due to the spin-coating method and the characteristics of the perovskite material, the front surface of the wide bandgap perovskite film is bonded to the sawtooth grating micro-nano structure, and the rear surface is a planar structure. The thickest part is 450nm, and the thinnest part is 300nm, obtaining a wide bandgap perovskite layer 400.
[0106] S5: A layer of C is evaporated on the wide bandgap perovskite film by thermal evaporation technology. 60 Electron transport layer, thickness is 20nm.
[0107] S6: Atomic layer deposition in C 60 A SnO2 electron transport layer with a thickness of 20 nm is deposited on the electron transport layer to obtain a second wide band gap sub-battery functional layer 500 .
[0108] S7: sputtering a layer of IZO thin film as a carrier recombination layer on the SnO2 electron transport layer by magnetron sputtering technology, with a thickness of 20 nm, to obtain a carrier recombination layer 600.
[0109] S8: coating a PEDOT:PSS hole transport layer on the IZO film with a thickness of 30 nm to obtain the first narrow bandgap sub-battery functional layer 700 .
[0110] S9: A narrow bandgap perovskite film is spin-coated on the PEDOT:PSS hole transport layer by a two-step method, and then the remaining solvent is evaporated by two-step annealing to obtain a narrow bandgap perovskite layer 800.
[0111] S10: Using thermal evaporation technology, a layer of C with a thickness of 20nm is evaporated on the narrow bandgap perovskite film. 60 An electron transport layer, a BCP film with a thickness of 7 nm, and a copper electrode with a thickness of 150 nm are formed to obtain a second narrow bandgap sub-battery functional layer 900 and a second electrode layer 1000.
[0112] Embodiment 5, this embodiment provides a method for preparing an all-perovskite tandem solar cell, which is used to prepare the all-perovskite tandem solar cell described in Embodiment 3, and the method comprises: S1: A sinusoidal grating micro-nano structure is etched on a photovoltaic glass substrate by electron beam lithography technology to obtain a transparent base layer 100 having a sinusoidal grating micro-nano structure on the back side.
[0113] S2: Sputter a layer of ITO transparent thin film electrode with a thickness of 150 nm on the photovoltaic glass with the sinusoidal grating micro-nano structure by magnetron sputtering technology. Due to the characteristics of magnetron sputtering technology, the thin film grows conformally with the sinusoidal grating structure to obtain the first electrode layer 200.
[0114] S3: Deposit a layer of NiO on the ITO transparent thin film electrode using atomic layer deposition technology x The hole transport layer has a thickness of 10 nm. Due to the characteristics of the atomic layer deposition technology, this thin film grows conformally with the ITO transparent thin film electrode to obtain the first wide bandgap sub-battery functional layer 300.
[0115] S4: Spin-coat a wide bandgap perovskite film on the substrate by a two-step method, and then evaporate the excess solvent by a two-step annealing method. Due to the spin-coating method and the characteristics of the perovskite material, the front surface of the wide bandgap perovskite film is bonded to the sinusoidal grating micro-nano structure, and the rear surface is a planar structure. The thickest part is 450nm, and the thinnest part is 300nm, obtaining a wide bandgap perovskite layer 400.
[0116] S5: A layer of C is evaporated on the wide bandgap perovskite film by thermal evaporation technology. 60 Electron transport layer, thickness is 20nm.
[0117] S6: Atomic layer deposition in C 60 A SnO2 electron transport layer with a thickness of 20 nm is deposited on the electron transport layer to obtain a second wide band gap sub-battery functional layer 500 .
[0118] S7: A layer of ultra-thin gold film is evaporated on the SnO2 electron transport layer by thermal evaporation technology as a tunnel junction, with a thickness of 0.4 nm, to obtain a carrier recombination layer 600.
[0119] S8: coating a PEDOT:PSS hole transport layer on the gold tunnel junction with a thickness of 30 nm to obtain the first narrow bandgap sub-battery functional layer 700 .
[0120] S9: A narrow bandgap perovskite film is spin-coated on the PEDOT:PSS hole transport layer by a two-step method, and then the remaining solvent is evaporated by two-step annealing to obtain a narrow bandgap perovskite layer 800.
[0121] S10: Using thermal evaporation technology, a layer of C with a thickness of 20nm is evaporated on the narrow bandgap perovskite film. 60 An electron transport layer, a BCP film with a thickness of 7 nm, and a copper electrode with a thickness of 150 nm are formed to obtain a second narrow bandgap sub-battery functional layer 900 and a second electrode layer 1000.
[0122] In summary, the beneficial effects of the present invention are: 1. The anti-reflection effect is stable and is suitable for all-perovskite tandem solar cells of various materials and configurations: Based on the precise analysis of the underlying physical principles of all-perovskite tandem solar cell devices, the anti-reflection and enhanced absorption of the entire working band are achieved from the underlying principles. This design idea can be applied to various all-perovskite tandem solar cell structures, and targeted micro-nano structure design is carried out to maximize the light absorption capacity of the solar tandem cell.
[0123] 2. Significantly improve the light absorption capacity of the entire working spectrum band and greatly increase the photocurrent: A fine micro-nano structure is designed on the rear surface of the glass on the light incident side. This micro-nano structure can effectively reduce the reflected light loss between the glass and the indium tin oxide transparent electrode in the entire working band, while breaking the enhanced reflected light loss caused by the internal optical coherent coupling of the stacked cell in the long-wave range, thereby achieving improved light absorption in the entire band.
[0124] 3. The device has a simple structure, is easy to prepare, and has high repeatability: When designing the specific configuration of the micro-nano structure, the difficulty and repeatability of the actual processing process and the effect achieved by the micro-nano structure are taken into comprehensive consideration. The designed micro-nano structure is suitable for actual mass production and has low cost.
[0125] 4. No additional process flow is required to make the perovskite and the micro-nano structure grow conformally, which significantly reduces the technical requirements and production costs of the production process: the all-perovskite solar tandem cells can be produced on the micro-nano structure designed by the present invention through common process technology and processes to achieve high light absorption effect in the entire working band, without introducing additional process flow, thus ensuring the efficiency of the preparation process.
[0126] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. An all-perovskite tandem solar cell, characterized in that: It comprises a transparent substrate layer (100), a first electrode layer (200) and a first wide bandgap sub-cell functional layer (300) which are sequentially stacked along the incident light direction; The side of the transparent base layer (100) away from the incident light is a velvet surface; The first electrode layer (200) is uniformly covered on the transparent substrate layer (100); The first wide bandgap sub-battery functional layer (300) is uniformly covered on the first electrode layer (200); The first electrode layer (200) is a transparent electrode.
2. The all-perovskite tandem solar cell according to claim 1, characterized in that: The cross-sectional shape of the transparent substrate layer (100) on the side away from the incident light changes periodically.
3. The all-perovskite tandem solar cell according to claim 1 or 2, characterized in that: The cross-sectional shape of the side of the transparent base layer (100) away from the incident light is sawtooth-shaped.
4. The all-perovskite tandem solar cell according to claim 3, characterized in that: The cross-sectional shape of the side of the transparent substrate layer (100) away from the incident light changes sinusoidally.
5. The all-perovskite tandem solar cell according to claim 1, characterized in that: It also includes a wide bandgap perovskite layer (400), a second wide bandgap sub-battery functional layer (500), a carrier recombination layer (600), a first narrow bandgap sub-battery functional layer (700), a narrow bandgap perovskite layer (800), a second narrow bandgap sub-battery functional layer (900), and a second electrode layer (1000) stacked in sequence on the first wide bandgap sub-battery functional layer (300).
6. The all-perovskite tandem solar cell according to claim 3, characterized in that: The cross-sectional shape of the side of the transparent base layer (100) away from the incident light is a periodic sawtooth structure with a period of 200 nm and a peak-to-valley height difference of 150 nm.
7. The all-perovskite tandem solar cell according to claim 4, characterized in that: The cross-sectional shape of the side of the transparent base layer (100) away from the incident light is a periodic sinusoidal structure with a period of 200 nm and a peak-to-valley height difference of 150 nm.
8. A method for preparing an all-perovskite tandem solar cell, characterized in that: include, Forming a velvet micro-nano structure on the side of the transparent base layer (100) away from the incident light; Conformally growing a first electrode layer (200) on the transparent base layer (100); A first wide bandgap sub-battery functional layer (300) is conformally grown on the first electrode layer (200).
9. The method for preparing the all-perovskite tandem solar cell according to claim 8, characterized in that: The velvet micro-nano structure is a periodic sawtooth structure.
10. The method for preparing the all-perovskite tandem solar cell according to claim 9, characterized in that: The velvet micro-nano structure is a periodic sinusoidal structure.
Citation Information
Patent Citations
Perovskite / perovskite laminated solar cell with inverted structure
CN114914365A
Texture ZAO transparent conductive film
CN201623164U
Perovskite battery of gradual change band gap
CN207320169U
Multi-junction solar cell, perovskite-crystalline silicon tandem cell, crystalline silicon cell, and preparation method therefor
WO2024027797A1
Cited By
Design method and system of full-perovskite laminated solar cell and solar cell
CN119808602A